Proceedings of the 25th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (IEEE Cat. No.0
DOI: 10.1109/iembs.2003.1280382
|View full text |Cite
|
Sign up to set email alerts
|

Bispectrum for the detection of the effect of photic and microwave stimulation on human EEG

Abstract: Absfrucf-The effects of microwave radiation on the electrical activity of human brain have been studied on a small group of young healthy volunteers. For estimation of the location of possible effects, the following EEG channels were utilized: F3, F4, T3, T4, 0 1 , 0 2 . The experiments included repeated microwave radiation at 450 MHz with modulating frequency 7 Hz and 16 Hz photic stimulation. For comparing the brain activity in different situations, three parameters from the EEG bispectrum were calculated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previously, several linear and non-linear methods were applied by our group to detect possible changes in EEG signals, using the same exposure conditions and an experimental protocol similar to that of this study, except for the use of photic stimulation (HINRIKUS et al, 2004;PARTS et al, 2003). In particular, linear statistical analysis has been applied to relative changes in EEG rhythms energy of the cycles with and without low-level modulated microwave exposure.…”
Section: Distinction Of Stressor Effectmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, several linear and non-linear methods were applied by our group to detect possible changes in EEG signals, using the same exposure conditions and an experimental protocol similar to that of this study, except for the use of photic stimulation (HINRIKUS et al, 2004;PARTS et al, 2003). In particular, linear statistical analysis has been applied to relative changes in EEG rhythms energy of the cycles with and without low-level modulated microwave exposure.…”
Section: Distinction Of Stressor Effectmentioning
confidence: 97%
“…We used modulated microwave radiation at a non-thermal level of field power density, identical to our previous studies (LASS et al, 2002;PARTS et al, 2003). Microwave exposure conditions were the same for all subjects.…”
Section: Microwave Exposurementioning
confidence: 99%
“…The 1 W output power was guided by a coaxial cable to the 13 cm quarter wave antenna, located 10 cm from the left side of the head. The field power density at the skin, estimated by the measured calibration curves, was 0.16 mW/cm 2 , SAR was about 0.35 W/kg [5]. …”
Section: Microwave Exposurementioning
confidence: 99%
“…It is difficult to detect small variations in the EEG signals on the background of their high natural variability. Manuscript Our previous studies on detection of the effect of microwave radiation on human EEG showed that some traditional methods for EEG analysis such as weighted spectral intensity, bispectrum or fractal dimension, usually successfully applied, did not provide distinction of small changes caused by microwave in EEG [5,6]. In the case of detection of small changes in stochastic signals the method of modulation with further integration of differences between the segments of signal with and without expected change would be useful.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous attempts on detection of the effect of microwave radiation on human EEG showed that some traditional methods of EEG analysis such as weighted spectral power of the EEG frequency bands, bispectrum or fractal dimension, usually successfully applied, did not provide reliable distinction of small changes in the EEG caused by the microwave radiation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%